TEACHERS AND NORMAL SCHOOLS IN THE COLOMBIAN CARIBBEAN REGION DURING FEDERAL REGIME - Alarcón Meneses, Luis (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This paper shows one of the main actors in the school scene of the Colombian Caribbean: the teacher, who played a major role in the educational project proposed by extreme liberals during federal regime. Indeed, for extreme liberals the best way to advance towards the consolidation of the republican regime had necessarily to make its way through the public instruction strengthening, to this end it was essential to grow teachers in specialized schools such as normal schools, which were also established in Cartagena, Santa Marta and Barranquilla during the second half of the 19th century. Certainly, normal schools were built in the main educational scene to make teachers professionals. Because of this, it is important to make a historical time line in order to know how were the dynamics of the educational process driven in the region by extremists and at the same time transport us to the core of educational space, i.e. beyond pedagogical speech, managers' and supervisors' rhetoric which sometimes it is observed by academic institutions from the outside; leaving a side the details about educational habits that took place.